Reducing and managing waste : implementing the Waste Prevention Programme and moving towards a 'zero waste' economy, 21st January 2014.: implementing the Waste Prevention Programme and moving towards a 'zero waste' economy, 21st January 2014. ([2014]) - Unknown
No abstract available